Comparative fertility and hatchability of broiler grandparent stocks in Bangladesh - Kakon, Md Tanbir Anjum; Shahid, Md Ahosanul Haque; Dutta, Amitush; Pinky, Samira Akter; Islam, Md Shafi; Hasnath, Md Rashed (Asian-Australasian Journal of Food Safety and Security, 2024)
Checking the fertility and hatchability of broiler grandparent lines is important for improving chicken production. The Cobb-500, Ross-308, and Indian River (IR) grandparent strains were studied to determine their initial egg weight, fertility, hatchability, embryonic mortality, hatching weight, and chick survival rates. We studied a total of 2700 eggs from three different age/treatment, each consisting of three replicates with 100 eggs for each of the three genotypes. Using an automated incubator, eggs were incubated. Cobb-500 had a significantly higher mean egg weight (67.52 g) at later stage of their age compared to Ross-308 (64.22 g) and IR (65.05 g). Study also found that a higher egg weight reflects a higher day-old chick weight. The fertility rates of the Ross-308, IR, and Cobb-500 genotypes were high at 35 weeks (96.00%, 87.00%, and 93.00%) but declined after 45 weeks (64.22%, 65.05%, and 67.52%), respectively. The hatchability of Ross-308, IR, and Cobb-500 eggs at 35 weeks was 85.00%, 75.00%, and 80.00%, respectively. By 45 weeks, all genotypes had higher hatchability, with Ross-308 having the highest at 89%. But at 55 weeks, all genotype showed lowest hatchability where IR was the lowest 67%. Statistically significant variations were observed across strains at later stage. As age increased, embryonic mortality and brood mortality were higher. Compared to the other two, Ross-308 showed the lowest mortality in both embryonic and brooding cases in all three stages of their age of life. However, the IR breed consistently displayed the highest mortality rate. Same pattern showed dead in shell and culling chick’s percentages. Strain-wise, the parameters differ from each other. However, regarding overall performance, the Ross-308 strain outperformed the other two strains. Asian Australas. J. Food Saf. Secur. 2024, 8(2), 48-57